On modelling the kinematics and evolutionary properties of pressure-pulse-driven impulsive solar jets - Singh B.; Sharma K.; Srivastava A.K. (My University, 2025)
In this paper, we describe the kinematical and evolutionary properties of the impulsive cool jets in the solar atmosphere using numerical simulation by Godunovtype PLUTO code at two different quiet-Sun magnetic field strengths (B = 56 gauss and B = 112 gauss). These types of chromospheric jets originate due to a pressure pulse, which mimics the after-effects of the localized heating in the lower solar atmosphere. These jets may be responsible for the transport of mass and energy in the localized upper atmosphere (i.e. corona). The detection of the height-time profiles for the jets, which were developed by imposing different pressure pulses, exhibit asymmetric near-parabolic behaviour. This infers that the upward motion of the jet occurs under the influence of pressure perturbation. However, its downward motion is not only governed by the gravitational free fall, but also by the complex plasma motions near its base under the effect of counter-propagating pulses. The maximum height and lifetime of the jets with respect to the strength of the pressure pulse show a linear increasing trend. This suggests that if the extent of the heating and, thus, the pressure perturbations are longer, then more longer chromospheric jets can be triggered from the same location in the chromosphere. For a certain amplitude of pressure pulse, the strong magnetic field configuration (B = 112 gauss) leads to more longer jets compared with the weaker field (B = 56 gauss). This suggests that the strong magnetic field guides the pressure-pulsedriven jets more efficiency towards the higher corona. In conclusion, our model mimics the properties and evolution of the variety of the cool impulsive jets in the chromosphere (e.g. macrospicules, network jets, isolated repeated cool jets, confined and small surges, and so on.). © Author(s) 2019.